2015
DOI: 10.1155/2016/6729268
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Physical Activity Downregulates Pax7 in Cancer Cachexia

Abstract: Emerging evidence suggests that the muscle microenvironment plays a prominent role in cancer cachexia. We recently showed that NF-kB-induced Pax7 overexpression impairs the myogenic potential of muscle precursors in cachectic mice, suggesting that lowering Pax7 expression may be beneficial in cancer cachexia. We evaluated the muscle regenerative potential after acute injury in C26 colon carcinoma tumor-bearing mice and healthy controls. Our analyses confirmed that the delayed muscle regeneration observed in mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 37 publications
1
36
1
Order By: Relevance
“…Resistance exercise has traditionally been proposed to fight cachexia and other forms of muscle atrophy because it is a type of exercise that increases muscle protein content balance, mass, strength and resistance to fatigue. Here, we show that wheel running, which shares the features of endurance training 44 , effectively counteracts muscle wasting; as opposed to activating pro-hypertrophic signaling pathways 14 , this type of exercise counteracts pro-atrophic NF-κB-dependent signaling 45 . We observed a significant increase in life span in wheel running C26-bearing mice.…”
Section: Discussionmentioning
confidence: 81%
“…Resistance exercise has traditionally been proposed to fight cachexia and other forms of muscle atrophy because it is a type of exercise that increases muscle protein content balance, mass, strength and resistance to fatigue. Here, we show that wheel running, which shares the features of endurance training 44 , effectively counteracts muscle wasting; as opposed to activating pro-hypertrophic signaling pathways 14 , this type of exercise counteracts pro-atrophic NF-κB-dependent signaling 45 . We observed a significant increase in life span in wheel running C26-bearing mice.…”
Section: Discussionmentioning
confidence: 81%
“…The SPA group condition was performed in a closed enriched environment (plastic box) with 60 cm in length, 30 cm in width and 45 cm in height ( Figure S2). This environment was composed of seesaw, wheel, balls, and tunnels (Coletti et al, 2016;Hutchinson, Avery, & VandeWoude, 2005;Van de Weerd et al, 2002). The condition of the RE group was performed using a vertical ladder 110 cm high with an inclination of 80 ° inclination ( Figure S1c).…”
Section: Groups Of Animalsmentioning
confidence: 99%
“…Worth noting, chemotherapy, used against cancer, induces cachexia and muscle wasting per se [17]. We and others have shown that cachexia is characterized by increased inflammatory markers in the skeletal muscle and by satellite cell activation [18,19]. However, in cachexia satellite cells fail to fuse with muscle fibers and their impairment contributes to muscle wasting [20][21][22].…”
Section: Introductionmentioning
confidence: 99%